A proposal for assessing campus landscape character for quality educational environment: case study of UPM Serdang / Osman Mohd Tahir and Lee Cheng Teik - Mohd Tahir, Osman; Lee, Cheng Teik (2008)
Campus landscape could act as a campus heritage and asset to the campus communities. Landscape areas and spaces are crucial facets of a campus's identity and serve as functional components of campus life. It provides place for study environment as well as place for student to escape physically and emotionally from study pressures. Campus Landscape Character Assessment is a potential tool to be used in planning for sustainable campus development and for characterizing the campus landscape environment. The study focused particularly in assessing UPM campus landscape in identifying its character and distinctiveness through classification of the Campus Landscape Character Types (CLCT). It will be conducted based on GIS application as decision supporting tool in quantitative data. The study will incorporate the stakeholders' perception in addressing the Campus Landscape Character Area (CLLA). Collaboration of both quantitative and qualitative data would be aided to the final output of this study in clarification of distinctive character of UPM context. Finally, it is hope that this study would encourage collaborative endeavour of planner and end users in understanding and managing the campus, as well as creating and shaping the ideal learning environment for Malaysian Campus.